Digital Media-Assisted Problem Based Learning Model: Students' Learning Outcomes and Science Literacy at Middle School - Alka, Muh; Ernawati, Ernawati (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Low scientific literacy and student learning outcomes in science subjects are often caused by conventional learning processes and the lack of technological integration in solving real-world problems. This study aims to analyze the effect of implementing the Problem-Based Learning (PBL) learning model assisted by digital media on students' learning outcomes and scientific literacy in the digestive system material. This study used a quantitative approach with a quasi-experimental nonequivalent control group design. The research subjects consisted of two eighth-grade classes in a public junior high school, where the experimental class implemented PBL assisted by digital media (n=30) and the control class used conventional learning (n=30). Data was collected through learning outcome tests and scientific literacy tests, then analyzed using an independent sample t-test. The results showed a statistically significant difference between students' learning outcomes and scientific literacy in the two classes (p < 0.001). The experimental class achieved an average posttest learning outcome of 82.10, higher than the control class's 74.30. For the scientific literacy variable, the experimental class achieved an average of 79.40, while the control class achieved 71.20. The effect sizes found were categorized as strong, namely 1.17 for learning outcomes and 1.16 for scientific literacy. This study proves that the integration of digital media in PBL syntax is effective in improving students' cognitive achievement and science process skills. This research provides a practical contribution for educators in implementing innovative learning strategies relevant to the digital era to create more applicable and meaningful science learning.